2002
DOI: 10.2320/matertrans.43.2193
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Ti-B-N Cast Alloys Prepared by Reactive Arc-Melting

Abstract: Ti-B-N cast alloys were prepared by a reactive arc-melting technique using elemental titanium and boron nitride powders. The alloys obtained were composites of titanium matrix containing nitrogen of 3 mol% or less and a small amount of TiB reinforcement. The microstructure of the matrix was a cellular structure consisting of elongated dislocation cells with 1-2 µm in width and 5-10 µm in length, for Ti-1B-1N alloy. The TiB particles were rod-like in shape with size of less than 0.5 µm in diameter and agglomera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…The titanium borides, especially TiB, are reported to form in a hexagonal pillar shape [26]. Morikawa et al [32] found clusters of TiB particles with rod-like shape along the grain boundary in the cast Tie1Be1N alloy. In the present work, relatively smaller features were observed; this is attributed to higher cooling rate of TIG compared to cast processing.…”
Section: Microstructuresmentioning
confidence: 99%
“…The titanium borides, especially TiB, are reported to form in a hexagonal pillar shape [26]. Morikawa et al [32] found clusters of TiB particles with rod-like shape along the grain boundary in the cast Tie1Be1N alloy. In the present work, relatively smaller features were observed; this is attributed to higher cooling rate of TIG compared to cast processing.…”
Section: Microstructuresmentioning
confidence: 99%
“…Reactive hot pressing (RHP) and casting processes have been reported to fabricate TiB-TMC parts to near net shapes. The effects of tailored microstructures on the mechanical properties have been investigated in both processes (Huang et al , 2012; Morikawa et al , 2002). These two traditional processes fabricate structure-restricted TiB-TMC parts with coarse microstructural grains at high-energy consumption (Zhang et al , 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A reactive arc-melting technique as reported elsewhere 9,17,18) was used to fabricate the Ti-50Al alloys and Ti-47Al-3W/Ti 2 AlC composites. The powders prepared are high purity elemental powders of titanium (99.5%, À350 mesh), aluminum (99.9%, À150 mesh), tungsten (99.95%, particle size; $1mm), and carbon (graphite, 99.99%, À400 mesh).…”
Section: Methodsmentioning
confidence: 99%